Implementasi Model Manajemen Perubahan Strategis Bank Pembiayaan Rakyat Syariah di Indonesia - Jas, Walneg Sopia; Maarif, M Syamsul; Syaukat, Yusman; Beik, Irfan Syauqi (School of Business, Bogor Agricultural University (SB-IPB), 2023)
The complex challenges faced by BPRS in Indonesia today to maintain their existence in the mid of competition and need to be overcome by planning for strategic changes. The purpose of this study is to analyze the complexity of the problems of BPRS in Indonesia today and Its sensitive elements through a structured picture approach, and to design a strategic change management’s model. The research was conducted in Indonesia, especially the Greater Jakarta, Surabaya, Bandung, Semarang and Yogyakarta by involving the management and managerial level at BPRS. The research was carried out in December 2021 to June 2022. Research data were obtained through primary data and secondary data. The research methodology used is mixed methods which is combination beetwen quantitave and qualitative methods, Soft System Methodology (SSM) Fuzzy AHP (F-AHP) and Fuzzy ISM (F-ISM). Based on the results of the SSM analysis, it is known that the current problematic situation faced by BPRS is technological disruption, market share, economic stability, low liquidity, pandemic disruption, human resources competence, segmentation rules and the absence of suitable product or service differentiation and unique. Based on the F-AHP analysis, the strategy that is considered the most reliable and a top priority in the strategic change management model strategy of BPRS in Indonesia is strengthening the policies and institutional regulations of the BPRS. The results of the F-ISM analysis show the most optimal institutional model and strategic change management model for Sharia Rural Banks in Indonesia. Keywords: BPRS, Change Management, Sharia, Fuzzy AHP,Fuzzy ISM